Announcing waiting time in emergency departments - Lariviere, Martin A. (SAGE Business Cases., 2019)
First National Healthcare (FNH) is one of the largest private hospital chains in the country. Its hospitals in the Western Florida region recently launched a highly successful marketing campaign that involved posting the current waiting times of their emergency departments on billboards. FNH hospitals in other regions are excited by the success of this campaign and want to follow suit, but the VP of quality assurance is concerned about the accuracy of the method of calculating waiting times. She is also uncertain whether the campaign's strategic objectives align with its actual implementation.